PENGUKURAN DAN UPAYA PENINGKATAN EFEKTIFITAS MESIN BIAS CUTTING DI PT. XYZ DENGAN MENGGUNAKAN METODE OEE DAN FMEA (Universitas Esa Unggul, 2018)
AbstractThe increasing number of Bus and truck type vehicles in Indonesia, the need for bias and radial tires will also increase. Increasing the need for bias and radial tires will add customer demand so that PT. XYZ should also increase production target in order to fulfill the customer demand. However, the fact that various problem factors can inhibit the production process itself as a result of low effectiveness in the production machines used so that the achievement of production targets is still far from expectation.This research aims to calculate and analyze the effectiveness of Cutting bias machine by using OEE method, identifying factors causing low effectiveness of bias Cutting machine and provide repair solution to increase effectiveness on Cutting bias machine. The research was conducted on Cutting bias division with the data used is engine Breakdown data, during engine operation, total production, time cycle, normal and raw as well as scrap data or reject production. The entire data is processed with the OEE method and analyzed by Pareto diagram, Fishbone diagram, quality matrix (CTQ), and FMEA.The results of this study showed that the average value of OEE engine Bias Cutting period in January – October 2016 was ABC-1 of 57.99%, ABC-2 of 62.58%, ABC-3 amounted to 54.01%, ABC-4 amounted to 58.27% and ABC-5 amounted to 59.80%. The cause of low effectiveness in Bias Cutting machine is the performance ratio caused by one of the causes of problems at reduced speed, which is often the frequency of switching roll in wind up alternately by 58,687 minutes. The proposed improvement is based on the largest risk value (RPN) with the FMEA method, which is 1.5 meters in length at the beginning of the liner (roll) is given the boundary (marking) in the form of colored lines and using the detection sensor diameter of the initial roll of liner, Each liner type is given a marking (color) at the edges of the liner according to the specifications of each size of the product and using the detecting sensor diameter rolls of liner cloth (roll) for each size product Bias Cutting,Each liner type is given a marking (color) at the edges of the liner according to the specifications of each size of the product and using the detecting sensor diameter rolls of liner cloth (roll) for each size product Bias Cutting, There is a speed control at the beginning of the roll so that the friction can be minimised and the buzzer as a detector when the speed when the liner initial roll exceeds the expected, making the work instruction (IK) on the operation of the apparatus to remove the loaded roll and the presence of a buzzer as an detector when the operator is wrong in operation of the appliance. Keywords: total productive maintenance (TPM), overall equipment effectiveness (OEE), bias cutting AbstrakSemakin meningkatnya jumlah kendaraan jenis Bus dan Truk di Indonesia, maka kebutuhan ban bias dan radial juga akan semakin meningkat. Meningkatnya kebutuhan ban bias dan radial akan menambah permintaan customer sehingga PT. XYZ juga harus meningkatkan target produksi agar dapat memenuhi permintaan customer tersebut. Namun, kenyataannya berbagai faktor masalah dapat menghambat proses produksi itu sendiri sebagai akibat rendahnya efektifitas pada mesin produksi yang digunakan sehingga pencapaian target produksi masih jauh dari harapan. Penelitian ini bertujuan untuk menghitung dan menganalisis efektifitas mesin Bias Cutting dengan menggunakan metode OEE, mengidentifikasi faktor- faktor penyebab rendahnya efektifitas mesin Bias Cutting dan memberikan solusi perbaikan untuk meningkatkan efektifitas pada mesin Bias Cutting. Penelitian ini dilakukan pada divisi Bias Cutting dengan data yang digunakan adalah data breakdown mesin, waktu operasi mesin, total produksi, waktu siklus, normal dan baku serta data scrap atau reject produksi. Keseluruhan data tersebut diolah dengan metode OEE dan dianalisis dengan diagram pareto, fishbone diagram, matrik kualitas (CTQ), dan FMEA. Hasil dari penelitian ini menunjukkan bahwa rata-rata nilai OEE mesin Bias Cutting periode bulan Januari – Oktober 2016 adalah ABC-1 sebesar 57,99 %, ABC-2 sebesar 62,58 %, ABC-3 sebesar 54,01 %, ABC-4 sebesar 58,27 % dan ABC-5 sebesar 59,80 %. Faktor penyebab rendahnya efektifitas pada mesin Bias Cutting adalah nilai performance ratio yang disebabkan oleh salah satu penyebab masalah pada reduced speed, yaitu seringnya frekuensi pergantian roll di wind up secara bergantian sebesar 58.687 menit. Adapun usulan perbaikan berdasarkan nilai resiko (RPN) terbesar dengan metode FMEA, yaitu setiap panjang 1,5 meter pada awal kain liner (roll) diberikan batasan (tanda) berupa garis berwarna dan menggunakan sensor pendeteksi besaran diameter gulungan awal liner (roll), setiap jenis kain liner diberikan tanda (warna) pada pinggir kain liner sesuai dengan spesifikasi setiap size produk dan menggunakan sensor pendeteksi diameter gulungan kain liner (roll) untuk setiap size produk Bias Cutting, adanya speed control saat awal gulungan agar gesekan dapat diminimalisir dan adanya buzzer sebagai pendeteksi apabila speed saat gulungan awal liner melebihi dari yang diharapkan, membuat Instruksi Kerja (IK) tentang pengoperasian alat bantu untuk mengangkat roll yang telah terisi ply dan adanya buzzer sebagai pendeteksi apabila operator salah dalam pengoperasian alat tersebut. Kata kunci : total productive maintenance (TPM), overall equipment effectiveness (OEE), bias cutting